2019
DOI: 10.3390/ijms20051055
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Novel R2R3-MYB Transcription factors, PsMYB114L and PsMYB12L, Related to Anthocyanin Biosynthesis in Paeonia suffruticosa

Abstract: Flower color is a charming phenotype with very important ornamental and commercial values. Anthocyanins play a critical role in determining flower color pattern formation, and their biosynthesis is typically regulated by R2R3-MYB transcription factors (TFs). Paeonia suffruticosa is a famous ornamental plant with colorful flowers. However, little is known about the R2R3-MYB TFs that regulate anthocyanin accumulation in P. suffruticosa. In the present study, two R2R3-MYB TFs, namely, PsMYB114L and PsMYB12L, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 69 publications
0
30
0
4
Order By: Relevance
“…Recent studies of purple head Chinese cabbage revealed that total anthocyanin content is associated with high expression of only BrMYB2 (Bra004162) among these three BrMYBs, accompanied by upregulation of BrTT8 and a series of ABGs, including BrF3'H, BrDFR, BrANS, BrUGTs, and BrGSTs 10,27 . Recent advances have shown that MYBs activate bHLHs and ABGs through strong interactions with bHLHs to promote anthocyanin biosynthesis in crop plants [38][39][40] . In purple cauliflower and red cabbage, BoMYB2 is responsible for the purple trait by interacting with BoHLHs and related ABGs [15][16][17] , and homologous comparisons showed that BrMYB2 is highly homologous with BoMYB2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of purple head Chinese cabbage revealed that total anthocyanin content is associated with high expression of only BrMYB2 (Bra004162) among these three BrMYBs, accompanied by upregulation of BrTT8 and a series of ABGs, including BrF3'H, BrDFR, BrANS, BrUGTs, and BrGSTs 10,27 . Recent advances have shown that MYBs activate bHLHs and ABGs through strong interactions with bHLHs to promote anthocyanin biosynthesis in crop plants [38][39][40] . In purple cauliflower and red cabbage, BoMYB2 is responsible for the purple trait by interacting with BoHLHs and related ABGs [15][16][17] , and homologous comparisons showed that BrMYB2 is highly homologous with BoMYB2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, conical epidermal cells contained significantly more anthocyanin and other flavonoids than flat epidermal cells in Antirrhinum petals [51]. In transgenic Arabidopsis plants, overexpression of PsMYB114L and of PsMYB12L caused a significantly higher accumulation of anthocyanins, resulting in purple-red leaves [52]. In Phalaenopsis orchids, PeMYB11-silencing resulted in the loss of anthocyanin content with flower colors fading from darkpurple to pink [2].…”
Section: The Color Of Different Regions Of Lily Petal Were Positivelymentioning
confidence: 99%
“…However, anthocyanin content in Paeonia flowers differs significantly from that of Ribes fruits, with peonidin, pelargonidin and cyanidin 3- and 3,5-glucosides being the main species in Paeonia [ 20 ]. Although anthocyanin-regulating MYBs and, to a lesser degree, the other regulators have been analyzed in many plants, such genes in Saxifragales were only recently identified in P. suffruticosa [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%